2006
DOI: 10.1097/01.mpg.0000228106.91240.5b
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Intervention in the First Months of Life

Abstract: Probiotic administration in the first months of life was well tolerated and did not significantly interfere with long-term composition or quantity of gut microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Altered microbiota containing fewer beneficial bacteria are suggested to provide inappropriate signals to mucosal immune cells leading to aberrant inflammatory responses and a loss of immune regulation. Studies have reported that prenatal and/or postnatal probiotic treatment with various Lactobacillus and Bifidobacterium species improved microbiota patterns (37, 38). Moreover, data from meta-analyses on the ability of probiotics to prevent allergic diseases are inconclusive, owing predominately to the heterogeneity in the study designs and probiotic used (39, 40).…”
Section: Discussionmentioning
confidence: 99%
“…Altered microbiota containing fewer beneficial bacteria are suggested to provide inappropriate signals to mucosal immune cells leading to aberrant inflammatory responses and a loss of immune regulation. Studies have reported that prenatal and/or postnatal probiotic treatment with various Lactobacillus and Bifidobacterium species improved microbiota patterns (37, 38). Moreover, data from meta-analyses on the ability of probiotics to prevent allergic diseases are inconclusive, owing predominately to the heterogeneity in the study designs and probiotic used (39, 40).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Roger et al (38) reported a greater diversity of Bifidobacterium populations in breast-fed than in formula-fed infants, an effect persisting up to 18 mo of age. On the other hand, Rinne et al (39) studied the effect of early administration of probiotics and could not find any significant interference with composition or quantity of gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of optimal timing and duration of intervention are also important issues in the RCTs of early probiotic supplementation for preventing CMS. Rinne et al [49] have demonstrated that probiotic administration during the last 6 mo of pregnancy and first 6 mo postpartum did not influence long term (2 years) composition of the infant gut flora. Perinatal metabolic programming and immune mediated effects on the infant gut flora by the administration of probiotic could explain the pathway of benefit [50] .…”
Section: Luoto 2010mentioning
confidence: 99%